Effectiveness of sucrose during the frozen storage of arazá (eugenia stipitata mcvaugh) pulp (2011)
The effects of sucrose on the quality of frozen arazá pulp were investigated. Five levels of sucrose (0, 5, 10, 20, and 30%) were evaluated in combination with freezing at low speed, storage during one month, and thawing at two different speeds. Sensory quality and water loss after centrifugation (WLAC) were evaluated in the samples. Before freezing sucrose addition(5-30%) to the pulp did not affect the sensory quality of the samples, but a negative effect on WLAC at 5-10% sucrose was observed. Furthermore, addition of 20-30% sucrose to arazá pulp, in combination with low speed-freezing, frozen storage, and low-speed-thawing, can be a useful technique to preserve the texture of arazá pulp. The described treatment gave results comparable to those obtained for the fresh pulp and much better than those obtained when freezing was done at high speed.